2014
DOI: 10.4330/wjc.v6.i7.539
|View full text |Cite
|
Sign up to set email alerts
|

Adipose tissue and vascular inflammation in coronary artery disease

Abstract: Obesity has become an important public health issue in Western and developing countries, with well known metabolic and cardiovascular complications. In the last decades, evidence have been growing about the active role of adipose tissue as an endocrine organ in determining these pathological consequences. As a consequence of the expansion of fat depots, in obese subjects, adipose tissue cells develope a phenotypic modification, which turns into a change of the secretory output. Adipocytokines produced by both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
35
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 176 publications
(186 reference statements)
3
35
0
2
Order By: Relevance
“…Furthermore, numerous animal studies have reported that adiponectin exerts direct anti-inflammatory, anti-atherogenic, antihypertensive (vasodilatory) and antidiabetic (insulinsensitizing) properties [11][12][13][14]. Nevertheless, even though adiponectin has been associated with well-known cardiovascular risk factors [4][5][6][8][9][10], a number of studies have failed to show any association between hypoadiponectinaemia and cardiovascular events in human beings, as summarized in three recent systematic reviews and meta-analyses [15][16][17]. In this context, the results linking adiponectin to hypertension in human beings have also been conflicting [18][19][20][21][22], and a possible direct effect of adiponectin on human resistance arteries has apparently never been tested.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, numerous animal studies have reported that adiponectin exerts direct anti-inflammatory, anti-atherogenic, antihypertensive (vasodilatory) and antidiabetic (insulinsensitizing) properties [11][12][13][14]. Nevertheless, even though adiponectin has been associated with well-known cardiovascular risk factors [4][5][6][8][9][10], a number of studies have failed to show any association between hypoadiponectinaemia and cardiovascular events in human beings, as summarized in three recent systematic reviews and meta-analyses [15][16][17]. In this context, the results linking adiponectin to hypertension in human beings have also been conflicting [18][19][20][21][22], and a possible direct effect of adiponectin on human resistance arteries has apparently never been tested.…”
mentioning
confidence: 99%
“…Adiponectin, a 244 amino acid protein, which is secreted from adipose tissue, is one of these adipocytokines [4][5][6][8][9][10]. Compared with other adipocytokines, adiponectin is distinct in the sense that lower (hypoadiponectinaemia) rather than higher (hyperadiponectinaemia) circulating concentrations of adiponectin have been associated with increased risk of overweight-related diseases [4][5][6][8][9][10].…”
mentioning
confidence: 99%
See 3 more Smart Citations